(untitled) (International Journal of Environment, 2013)
The small-scale (artisanal) fisheries in Zimbabwe play an important role in income-generation and food security at the household level. This sector has the potential to significantly increase its contribution to household income and food security if more effective fisheries management strategies are put in place. Historically, fisheries management has adopted a centralised “Top-down” approach. This approach has had very limited effectiveness. Over the last decade, efforts have been made to implement co-management in the fisheries sector. Several factors have hampered the success of fisheries co-management in the artisanal fishery. These factors have been institutional, ecological, human and financial. This paper discusses these factors and proposes possible solutions. A more innovative and effective fisheries management approach is also proposed. DOI: http://dx.doi.org/10.3126/ije.v1i1.8526 International Journal of Environment Vol.1(1) 2013: 29-45